Magical realism in Salman Rushdie’s Midnight’s Children and Italo Calvino’s Invisible Cities - Tasnim, Humyra (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.